Board attributes and foreign shareholdings in Malaysian listed firms - Yatim, Puan; Mohd Iskandar, Takiah; Nga, Elsie (Springer US, 2014)
This study examines the association between foreign shareholdings and several characteristics of board of directors in the context of a developing capital market. Using data of 777 listed firms on Bursa Malaysia for the financial year 2008, the study predicts that foreign shareholdings are positively related to board independence, multiple directorships, and financial literacy of the board of directors. The study finds a strong positive relationship between multiple directorships and foreign shareholdings. Contrary to our expectation, the association between board financial literacy and foreign shareholdings is negative and significant. With regard to the link between board independence and foreign shareholdings, we find weak evidence to support our prediction that there is positive relationship between board independence and foreign shareholdings. The multivariate results also show strong positive relationships between foreign shareholdings and number of foreign directors on boards, and between foreign shareholdings and audit quality. The study also documents a significant negative association between foreign shareholdings and firm size, and between foreign shareholdings and book-to-market ratio. The findings of the study supports the view that multiple directorships is an important asset to firms in emerging markets partly due to limited pool of potential talents and experts which in turn could signal reputational capital and quality of directors. Since there is a mandated presence of finance and accounting qualified director on the audit committee, foreign shareholders can somewhat rely on the oversight of audit committee instead of depending entirely on the board of directors for the quality of financial statements and financial reporting oversight. Finally, the presence of foreign directors on a board of directors may signal a firm’s commitment to adopt good corporate governance practices. It is also possible that foreign investors can influence corporate governance through their participation on the board of directors.